S-Equol mitigates motivational deficits and dysregulation associated with HIV-1 - Kristen A. McLaurin (Nature Portfolio, 2021)
Abstract Motivational deficits (e.g., apathy) and dysregulation (e.g., addiction) in HIV-1 seropositive individuals, despite treatment with combination antiretroviral therapy, necessitates the development of innovative adjunctive therapeutics. S-Equol (SE), a selective estrogen receptor β agonist, has been implicated as a neuroprotective and/or neurorestorative therapeutic for HIV-1 associated neurocognitive disorders (HAND); its therapeutic utility for motivational alterations, however, has yet to be systematically evaluated. Thus, HIV-1 transgenic (Tg) and control animals were treated with either a daily oral dose of SE (0.2 mg) or vehicle and assessed in a series of tasks to evaluate goal-directed and drug-seeking behavior. First, at the genotypic level, motivational deficits in HIV-1 Tg rats treated with vehicle were characterized by a diminished reinforcing efficacy of, and sensitivity to, sucrose. Motivational dysregulation was evidenced by enhanced drug-seeking for cocaine relative to control animals treated with vehicle. Second, treatment with SE ameliorated both motivational deficits and dysregulation in HIV-1 Tg rats. Following a history of cocaine self-administration, HIV-1 Tg animals treated with vehicle exhibited lower levels of dendritic branching and a shift towards longer dendritic spines with decreased head diameter. Treatment with SE, however, led to long-term enhancements in dendritic spine morphology in HIV-1 Tg animals supporting a potential underlying basis by which SE exerts its therapeutic effects. Taken together, SE restored motivated behavior in the HIV-1 Tg rat, expanding the potential clinical utility of SE to include both neurocognitive and affective alterations.